Pengaruh Bermain Plastisin terhadap Perkembangan Motorik Halus pada Anak PRA Sekolah - Rewinda Avin Pangestika; Erni Setiyorini (STIKes Patria Husada Blitar, 2015)
Preschool children are often referred to as the golden period. During this period of growth and development of the child's intelligence is growing very rapidly, fine and gross motor development, ntelektual, moral, social, emotional and language. the phenomenon of the problem is found in fine motor development of pre-school age children, such as writing / drawing made students still neat, hold objects often fall and finger movements not flexible. The aims of this study was to determine the effect on the development of plasticine play to fine motor on pre-school children. Designs in this study was pre-experimental pre-post test design. The population in this study were 85 children in Kindergarten AL - Hidayah Tawangsari GARUM. Purposive sampling with a sample of 20 children. The data analysis technique t-test. The results showed that the p value (sig 2 tailed) = 0.000, which means playing plasticine influence on the development of fine motor skills of pre-school age children. Expected parents and kindergarten teachers actively involved in the stimulation of child development activities to achieve optimal development.